Service Quality Dan Customer Satisfaction Serta Pengaruhnya Terhadap Loyalitas Konsumen Pada CV Jaya Motor Bekasi - Nurvi Oktiani; Indyah Setyorini (Widya Cipta - Jurnal Sekretari dan Manajemen, 2018)
Services are activities undertaken by a person or group of people on the basis of a material factor through certain system, procedures and methods in order to fulfill the interest of others in accordance with their rights. To find out customer response will service motorcycle service at CV Jaya Motor, the authors conducted quantitative research three variables consist of Service Quality, Customer Satisfaction, through the method of distributing questionnaires from 50 respondents. The research uses calculations through software SPSS version 23, for the analytic of data is used Multiple Regression consist of the Classical assumption test, multikolinearitas, Normality, Heteroskedastisitas, Autokorelasi, from the Classical assumption test can describe there is no multikolinearitas, Normality, Heteroskedastisitas, Autokorelasi symptoms, partial correlations independen variabels can be describe between service quality and customer satisfaction have low correlation, which is consist of 0.098 and 0,107, beside that for coefficient determination can be explained 58,7%, and regression model can be describe for service quality variables  Ү : 7,916 + 0,264 Customer Satisfaction: Ү : (7,916 + 0,264) + 0,264 X2, and model regression for service quality and customer satisfaction toward loyality can be explained : Y: 7,916 + 0,264 X1+0,264 X2 , the finally CV Jayaa Motor Bekasi must give attention toward service quality and customer satisfaction, because the result have been low correlation and give more impact for loyality